The Use of Rewards to Increase and Decrease Trust: Mediating Processes and Differential Effects - FERRIN, Donald L. (Institutional Knowledge at Singapore Management University, 2003)
Hypotheses asserting that reward structures - an omnipresent element of the work context - have a strong influence on interpersonal trust are tested, and the cognitive and behavioral routes through which the effects may occur are explored. Specifically, attribution theory is used to identify several core processes including social perception, self-perception, and attributional biases that may explain trust development. A 3 x 2 experimental design in a problem-solving task was used to examine the hypotheses. The results suggest that reward structures have a strong influence on trust, and that the effect is mediated by causal schemas, suspicion effects, and self-perception. Some support was also found for the prediction that the impact of mixed reward structures on trust is biased by individuals' preexisting expectations about their partners' trustworthiness. The theory and results suggest that attribution theory provides a useful framework for understanding the complex, diverse, and multiple routes through which trust may develop.